On the Relationship Between Offshore Geodetic Coverage and Slip Model Uncertainty: Analog Megathrust Earthquake Case Studies. Issue 15 (3rd August 2020) - Kosari, Ehsan; Rosenau, Matthias; Bedford, Jonathan; Rudolf, Michael; Oncken, Onno
Abstract: We apply a geodetic slip inversion technique to analog subduction megathrust earthquakes to demonstrate how limited offshore geodetic coverage affects coseismic slip models. We analyzed two archetypical megathrust earthquakes: trench‐breaking and non‐trench‐breaking earthquakes. Slip inversion models of analog earthquakes show quantitative and qualitative changes as a function of offshore coverage. Shallow slip cannot be resolved if the observation coverage of the offshore segment is <50%. Moreover, the slip pattern of shallow events flips from landward to trenchward skewed as offshore coverage reduces to <40%. The estimated slip for both event types converges to a similar unimodal pattern when there is no offshore coverage. We infer 5–20% slip overestimation when the observations are above the high slipping zone during trench‐breaking events versus 5–10% underestimation during non‐trench‐breaking events if observations are land limited. The moment magnitude derived for trench‐breaking ruptures might be significantly affected (ΔMw 0.5). Plain Language Summary: The largest earthquakes on the world generally occur at convergent plate boundaries in subduction zones where two tectonic plates meet, and they pose a destructive threat by generating severe ground motion and devastating tsunamis. The source of the earthquakes is mostly located offshore, while the underwater sources are still deficiently instrumented. By simplifying the subduction system at the scale of an analog setup in the laboratory, we shed light on how insufficient monitoring of surface displacement near the trench could critically increase the uncertainty of inferring fault movement, called slip. Hence, this uncertainty can highly influence the estimation of slip distribution on the fault plane during an earthquake. We quantitatively and qualitatively highlighted that the lack of seafloor displacement measurements can overestimate/underestimate the calculated slip and infer an inaccurate slip distribution on a fault plane. Consequently, the imprecise estimation of slip distribution may lead to an unrealistic earthquake hazard assessment and real‐time tsunami prediction. Key Points: Analog earthquake experiments provide case studies to evaluate the linkage between offshore geodetic observations and coseismic slip models Slip inversion models of analog earthquakes show quantitative and qualitative changes as a function of offshore geodetic coverage Inverted slip for trench‐breaking and non‐trench‐breaking events converges to a similar pattern when there is no offshore geodetic coverage